Evaluation of a Slipped Capital Femoral Epiphysis Virtual Reality Surgical Simulation for the Orthopaedic Trainee. (25th April 2022) - Margalit, Adam; Suresh, Krishna V.; Marrache, Majd; Lentz, Jonathon M.; Lee, Rushyuan; Tis, John; Varghese, Ranjit; Hayashi, Brooke; Jain, Amit; Laporte, Dawn
Abstract : Objective: The purpose of this study was to compare outcomes between orthopaedic trainees using various preoperative training platforms (physical simulation [PS], virtual reality [VR], and reading/videos) in a slipped capital femoral epiphysis model. Methods: Participants were randomly assigned to one of the three groups: (1) reading/video control group (n = 7), (2) VR group (n = 7), or (3) PS group (n = 7). Participants in the VR group completed a VR slipped capital femoral epiphysis module while participants in the PS group practiced the placement of a screw in the physical module before evaluation of percutaneous screw placement in the PS model. Outcomes evaluated included overall surgical time, amount of fluoroscopy, Global Rating Scale score, radiographic screw position, physical screw accuracy, presence of breeching of the articular surface or femoral neck, and overall platform rating (0 to 10). Results: No difference was observed in surgical time, Global Rating Scale score, radiographic or physical accuracy of screw position, or articular surface breaching between the groups. Subjectively, there was a difference in utility of platform rating between the groups (PS: 10 ± 0, VR: 7 ± 2, and control: 6 ± 1, P = 0.001). Conclusion: Training with VR was subjectively rated higher in value compared with reading/video methods and had similar performance outcomes compared with training with PS.